(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
1 Problem statement This article first notes the important perspectives from social security experts concerning the instruments used to improve the operations for handling disability grants. The discourse ensued critically evaluates the frameworks, policies, system inaccuracies and efforts made by various government relating to the operations for handling disability grants across the globe to improve the instruments of the South Africa’s Social Security Agency used when disability grants are paid out to grantees. Sociologists in diverse areas of social security grants recognised the merits and demerits of the disability grant mechanisms, inefficacy experienced in grant distributions and the need for further employee training that is suitable for the appreciation of decisive service delivery strategies, capacitation, and participation of confederate (s), in all manner of social security establishments. Methods Utilising the qualitative paradigm and considering the concepts used in critical theory, this desktop research posits that, the disability grants policy implementers have a significant role to play in supporting a common purpose from the policymakers towards efficiently providing this form of government social support to grantees. 2 Results Although there are numberless actors who have been put in place by various social security agency model-based governance structures, which to a certain extent have hesitant strategic needs and consciousness, however there are more gaps in most of the instruments that have been adapted by the South African government to disburse disability grants that persistently engulf the system. 3 Conclusion To this end, it is important for the South African government situated at the South African Social Security Agency (SASSA), to pay attention to these instruments by evaluating their usability while paying social grants to maintain exacting skill, give employee attention and manage the scarce resources as part of enhancing social security philosophy for service delivery betterment.